RONDO'S MUSIC SECTIONAL FORM AND STRUCTURE "ALLA TURCA" BY WA. MOZART - Ance Juliet Panggabean; Robby Ferdian (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2023)
Abstract The Form and Sectional Structure of “Alla Turca” Rondo Music by WA. Mozart. The basic method that will be applied in this research is a qualitative descriptive method. In addition, the approach method used was the library method so that it was found and produced the Sectional Forms and Structures of WA's Rondo "Alla Turca" Music. Mozart. famous for its characteristic piano music, its musical form has a distinctive classical Rondo structure pattern, A B C B A B' and Coda. In addition to the typical 'brilliant' Rondo Form structure in Baroque terms, the use of chord levels (harmony progression) and rhythmic playing makes Rondo's music more lively, fast, and joyful. The sectional structure in Rondo Alla Turca Music by W. A. Mozart, the basis of the scale is diatonic-tonality, the basis of harmony is tri- voice major and minor, the rhythmic basis is duple and triple and symmetrical patterns, while the cadence (V-I or I-V-I), (V- VII7), (IV-I), (V-VI), (IV6-V-II). Form and sectional structure of Alla Turca rondo music. needs to be analyzed to describe music through forms, melodic sequences, tones, rhythms and harmonies that form a unified composition. This is done because music analysis is an important part of music theory, directed towards an approach towards musical understanding to be able to lead to understanding. In the listening process, the ability to follow a melodic groove in a musical pattern in a musical composition becomes a very important fundamental thing. In order to gain an understanding and understanding of the form and sectional structure of Alla Turca's rondo music, one must start from musical grammar, compositional techniques, form, structure, harmony, musical style.Keywords: Form; Sectional Structure; Music; RondoBENTUK DAN STRUKTUR SEKSIONAL MUSIK RONDO" ALLA TURCA" KARYA W.A MOZARTAbstrakBentuk dan Struktur Seksional Musik Rondo “Alla Turca” Karya WA. Mozart. Teknik analisis data adalah deskriptif kualitatif yang merupakan metode penelitian yang menganalisis tentang persepsi untuk mendapatkan informasi lengkap tentang bentuk dan struktur seksional musik rondo “Alla Turca” karya WA. Mozart. Terkenal dengan ciri khas musik piano, bentuk musikalnya memiliki pola struktur Rondo Klasik yang khas, A B C B A B’ dan Coda. Selain pola struktur Rondo Form yang khas ‘brilliant’ dalam istilah Barok, penggunaan tingkat akor (progressi harmoni) dan permainan ritme menjadikan musik Rondo ini lebih lincah, cepat, gembira. Struktur seksional dalam musik Rondo Alla Turca Karya W. A. Mozart, dasar tangga nada adalah tonalitas-diatonis, dasar harmoni tri suara mayor dan minor, dasar ritmis adalah duple dan triple serta pola-pola simetris, sedangakn kadens (V-I atau I-V-I), (V-VII7), (IV-I), (V-VI), (IV6-V-II). Bentuk dan struktur seksional musik rondo Alla Turca karya WA. Mozart penting dilakukan analisis untuk menguraikan musik melalui bentuk, rangkaian melodi, jalinan nada, ritme dan harmoni yang menjadi kesatuan komposisi. Hal ini dilakukan karena analisis musik adalah ilmu yang mempelajari hubungan antar elemen musik yang memperhatikan unsur musik yaitu, melodi, ritme dan harmoni secara detail yang menyusun karya tersebut.Untuk memperoleh pengertian dan pemahaman tentang bentuk dan struktur seksional musik rondo Alla Turca harus bertitik tolak dari gramatika musik, teknik komposisi, bentuk, struktur, harmoni, gaya musik.Kata Kunci:  Bentuk; Struktur seksional; Musik; Rondo